A wall solar chimney to ventilate multi-zone buildings. (October 2021) - Zhang, Haihua; Tao, Yao; Nguyen, Kate; Han, Fengling; Li, Jie; Shi, Long
Abstract: Although solar chimneys have been extensively investigated, their performance in multi-zone buildings have been overlooked previously. This study aims to examine the airflow characteristics inside a wall solar chimney and the attached ventilated multiple zones, together with the solar chimney performance, under various configurations ( i.e., chimney cavity and room) and external environment ( i.e., solar radiation intensity). The critical geometrical parameters of solar chimney and building layouts are then suggested based on the trade-offs between the buoyant flow patterns and the volumetric flow rate. Like those single zone applications, an increase in the chimney height and inlet location (until the middle height of the wall) results in a straight improvement in the airflow rate. By increasing the chimney height from 3.0 to 5.0 m, the ventilation capacity increases by about 90%; and moving the air inlet upward can get a 57.28% improvement of the ventilation rate. The maximum airflow rate in this study was observed for a solar chimney with a cavity gap of 0.2 m and an inlet size of 0.2 m, while enlarging the window area enhances the volume flow rate by up to 14.98%. In addition, when the cavity gap and inlet size exceed the optimal value, their influences on the airflow rate are observed insignificant, and the growth rate of volume flow rate decreases gradually. The multiple rooms with different aspect ratios seem to show a limited impact on the ventilation performance. The volume flow of four groups of room layouts shows a fluctuation of within 5%. The velocity distribution of the long and narrow room layout shows an average improvement of 2.5% than that of the two-room with a significant difference in width.